2014
DOI: 10.3923/pjbs.2014.964.977
|View full text |Cite
|
Sign up to set email alerts
|

Ameliorating Role of Rutin on Oxidative Stress Induced by Iron Overload in Hepatic Tissue of Rats

Abstract: Iron is an essential element that participates in several metabolic activities of cells; however, excess iron is a major cause of iron-induced oxidative stress and several human diseases. Natural flavonoids, as rutin, are well-known antioxidants and could be efficient protective agents. Therefore, the present study was undertaken to evaluate the protective influence of rutin supplementation to improve rat antioxidant systems against IOL-induced hepatic oxidative stress. Sixty male albino rats were randomly div… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
32
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(36 citation statements)
references
References 85 publications
3
32
0
1
Order By: Relevance
“…65,66 Rutin and phenolic acids increase antioxidant enzymes activities in several studies. 67,68 Silymarinprotected group showed the significant elevation in SOD, GST, GPx, and CAT activities revealing its antioxidant activity. 56,69 This may be due to its phenolic nature, which makes it able to donate electrons to stabilize free radicals and ROS leading to an enhanced DENA detoxification, elimination and reduction of carcinogen-DNA adducts formation.…”
Section: Histopathological Studiesmentioning
confidence: 97%
“…65,66 Rutin and phenolic acids increase antioxidant enzymes activities in several studies. 67,68 Silymarinprotected group showed the significant elevation in SOD, GST, GPx, and CAT activities revealing its antioxidant activity. 56,69 This may be due to its phenolic nature, which makes it able to donate electrons to stabilize free radicals and ROS leading to an enhanced DENA detoxification, elimination and reduction of carcinogen-DNA adducts formation.…”
Section: Histopathological Studiesmentioning
confidence: 97%
“…Results reported by Gavin et al and Shengjiang Guan et al indicated dysfunction of heart and kidney in iron overload (2,33). In the current study, after injection of iron dextran, kidney histological damage was observed, yet treatJundishapur J Nat Pharm Prod.…”
mentioning
confidence: 55%
“…The role of iron in the development of hepatic injuries in several clinical and experimental conditions has commonly been studied by induction of an iron overload condition (29)(30)(31)(32)(33).…”
Section: Discussionmentioning
confidence: 99%
“…These include positions between the 4-oxo and the 3-or 5-OH groups that can form complexes with a binding stoichiometry of 1:1 or 1:2, metal/myricetin [43,44]. Similarly, a glycoside, rutin ameliorated oxidative stress induced by iron overloaded in hepatic tissue of rats [45]. It is to be noted that myricetin and rutin were the major flavonoids detected in fenugreek seeds ( Table 1).…”
Section: Ferrous Ion Chelating Activitymentioning
confidence: 98%